Modification of the activity approach to the formation of learning activity in junior schoolchildren at the beginning of the XX-XXI century - Нікітіна, О. О. (Educational Dimension, 2012)
Nikitina Е. Modification of the activity approach to the formation of learning activity in junior schoolchildren at the beginning of the XX-XXI century. In the article features of modification of a deyatelnostny approach and value of its variations for formation of complete educational activity of pupils of primary school are considered.